INOVASI LAYANAN MPOSPAY DAN FREE PICK UP POS INDONESIA DALAM PENINGKATAN KUALITAS PELAYANAN (Studi Pada Kantor Pos Semarang 50000) - Warsono, Hardi; Qurniawati, Desti Relinda; Sitorus, Herta; Fajar S., Soni Mukhammad (JPSI (Journal of Public Sector Innovations), 2018)
Non-monoplistic public services must continuously innovate services in order to remain competitive with its competitors and can satisfy its customers. PT Pos Indonesia as one of the state-owned enterprises in Indonesia is also faced with the demand to innovate so as not to lose with the private competitors. PT Pos is one of the BUMN that provide services expedition on the community, among the many services similar services. This study aims to determine the service innovation and quality of service at the Post Office Semarang 50000. Research conducted with qualitative. The main theory to measure the quality of service is based on the opinion of A Parasuraman that measures the quality of service from indicators: tangibles, reliability, responsiveness, assurance and empathy. The result of the research shows that service innovation at PT Pos Indonesia for the improvement of service quality is good enough, but there are some deficiencies such as: the delivery of new innovation information from the officer to the customer is still less effective, so this innovation seems not optimal. In general the quality of service is good, ranging from the response officers, facilities provided, guarantees and services provided. There are still shortcomings in the delivery of information that has not been effective to the customer. This study recommends the need for accurate and detailed information about the innovations made.